Negotiating the Cultural Values in Indonesian Mixed Nationality Marriage toward Society 5.0 - Ulani Yunus; Bhernadetta Pravita Wahyuningtyas; Lea Simek (Ikatan Sarjana Komunikasi Indonesia, 2022)
Indonesia has become integrated into the global economy. As a result, many expatriates are employed in Indonesia and married Indonesian women.Â This research aims to find out how is cross-cultural communication among members of PERCA (intermarriage community) toward society 5.0. The methodology of this research is descriptive qualitative based on interviews with primary sources, literature and observation and analysis based on the existing concept. This research was conducted by comparing it with previous studies conducted in other countries. The results of this research show there are diverse languages and cultures, including those of Java, Bali, and Padang used in intermarriage. This research concluded that families use both English and Indonesia language in daily activities, these women accept their fate to marry foreign men on condition that they follow their wivesâ€™ religion, although in practice the husbands are not supposed to run with obedience as her. Children are educated according to their mother's religion and study in an international school with the ultimate goal of studying and working abroad such as in the United States or their fatherâ€™s country of origin.